(untitled) (Research, Society and Development, 2021)
Objective: To analyze the vaccination coverage for polio and the surveillance strategy of Acute Flaccid Paralysis (FAP) in the Brazilian Amazon, from 2010 to 2019. Methodology: Cross-sectional observational study with descriptive and analytical aspect of the time series of routine vaccination coverage for Inactivated Polio Vaccine (VIP) and Oral Polio Vaccine (PWV) and the incidence coefficient/100,000 inhabitants of the PFA notifications from 2010 to 2019. Results: Low vaccine coverage was observed for both vaccines in the states and municipalities, maximum mean for OR and minimum for PA: 104.2% and 78.7% for VIP; 84.1% and 55.1% for PWV, respectively, presenting heterogeneity and dropout rate for both vaccines and all states classified as very high risk for polio transmission. Regarding the notifications of PFA, there were 591 reported cases, with a higher incidence coefficient in the range of 1 to 4 years (13.8/100,000inhab), with most of the outcomes without confirmation for wild poliovirus, therefore, discarded. However, it calls attention to "vaccine-associated" and "inconclusive" cases that correspond to the sum of 2% and 5.7% in the analyzed period, respectively. Conclusion: We observed low vaccine coverage for VIP and PWV, lack of homogeneity in vaccine coverage, increased rate of dropout, and high risk of disease transmission, in addition to low-sensitivity surveillance of AFP. Thus, increased vulnerability and susceptibility to poliovirus reintroduction.